2001
DOI: 10.1016/s1097-2765(01)00285-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Specific Activation of Rac Controls Progression through the G1 Phase of the Cell Cycle

Abstract: Adhesion to fibronectin through the alpha5beta1 integrin enables endothelial cells to proliferate in response to growth factors, whereas adhesion to laminin through alpha2beta1 results in growth arrest under the same conditions. On laminin, endothelial cells fail to translate Cyclin D1 mRNA and activate CDK4 and CDK6. Activated Rac, but not MEK1, PI-3K, or Akt, rescues biosynthesis of cyclin D1 and progression through the G(1) phase. Conversely, dominant negative Rac prevents these events on fibronectin. Mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
201
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(221 citation statements)
references
References 54 publications
15
201
1
4
Order By: Relevance
“…In agreement with the work of Mettouchi et al (38), tyrosinephosphorylated caveolin-1 (Tyr(P) 14 ) was easily detected in cells seeded on FN-coated plates and was localized along the cell periphery, as expected. However, little or no phosphorylated caveolin-1 (Tyr(P) 14 ) was detected in cells seeded on PLLcoated plates (Fig.…”
Section: Identification Of Sh2 Domain Containing Binding Partners Forsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the work of Mettouchi et al (38), tyrosinephosphorylated caveolin-1 (Tyr(P) 14 ) was easily detected in cells seeded on FN-coated plates and was localized along the cell periphery, as expected. However, little or no phosphorylated caveolin-1 (Tyr(P) 14 ) was detected in cells seeded on PLLcoated plates (Fig.…”
Section: Identification Of Sh2 Domain Containing Binding Partners Forsupporting
confidence: 92%
“…Recently, Mettouchi et al (38) showed that the tyrosine phosphorylation of caveolin-1 (Tyr(P) 14 ) can also be stimulated by integrin ligation. By the use of immunostaining techniques on human umbilical vein endothelial cells, they showed that cellular adhesion to fibronectin led to the accumulation of phosphocaveolin-1 (Tyr(P) 14 ) at focal adhesions.…”
Section: Identification Of Sh2 Domain Containing Binding Partners Formentioning
confidence: 99%
“…Cell division is a highly regulated process that is modulated in response to adverse conditions including ionizing radiation [40,41]. Signaling via adhesion of integrins to laminin 5 is known to be involved in progression through the G1 phase of the cell cycle [32,33,42] and other integrin/ligand interactions in the G2/M transition [35,43]. Our data support adhesion-mediated regulation of the G2 phase through the integrin ligand laminin 5.…”
Section: Discussionsupporting
confidence: 74%
“…For examples, growth suppressive treatments decreased cyclin D1 protein synthesis with minimal changes in message levels (Brewer and Diehl, 2000;Mettouchi et al, 2001;Muise-Helmericks et al, 1998;Palakurthi et al, 2000;Pervin et al, 2001). Fumonisin B1, a carcinogenic mycotoxin, stabilizes cyclin D1 protein resulting in high levels of protein expression without a change in message levels (Ramljak et al, 2000).…”
Section: Discussionmentioning
confidence: 99%